Effect of Vietnamese coriander (Persicaria odorata), turmeric (Curcuma longa) and asam gelugor (Garcinia atroviridis) leaf on the microbiological quality of gulai tempoyak paste - Abdul Aris, Mohd Hafiz; Lee, Hai Yen; Hussain, N.; Ghazali, Hazrina; Md. Noordin, Wan Norhana; Mahyudin, Nor Ainy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The objective of this study was to determine microbiological quality of gulai tempoyak paste (GTP) added with three different leaf; Vietnamese coriander, turmeric and asam gelugor. The GTP was cooked for 10 minutes with control temperature (60-70°C) and the leaf were added at 2, 5 and 8 minutes during the cooking time to give exposure times of 8, 5 and 2 minutes of the leaf to GTP. GTP without addition of leaf was treated as control and all the prepared GTPs were stored at 30°C for 2 days before analysed using total plate count (TPC) and yeast and mould count (YMC). The addition of asam gelugor leaf to GTP for 5 minutes of the cooking period significantly (p < 0.05) reduced TPC (log10 3.54 CFU/g) compared to Vietnamese coriander (log10 4.67 CFU/g) and turmeric leaf (log10 4.70 CFU/g). Asam gelugor leaf also showed a significant difference in TPC reduction (log10 4.44 CFU/g) when added to GTP for 8 minutes compared to Vietnamese coriander (log10 5.10 CFU/g), but was insignificant to turmeric leaf (log10 4.71 CFU/g). In conclusion, there are significant effects on microbiological quality of GTP when added with Vietnamese coriander, turmeric and asam gelugor leaf at different exposure time based on TPC and YMC.